2020
DOI: 10.14218/erhm.2020.00011
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Near Miss and Its Associated Factors at Injibara General Hospital, Awi Zone, Northwest Ethiopia, 2019

Abstract: Background and objectives: There are many newborns who suffer a life-threatening complication in many lowresource countries. Neonatal near miss has been proposed as a tool to evaluate and improve the quality of neonatal care. However, there has been limited evidence on magnitude of neonatal near miss and determinant factors in Ethiopia. The aim of this study was to assess proportion and associated factors of neonatal near miss among neonates delivered at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…In line with several studies, 16 , 19 , 22 , 30 we found that NNM was higher among primiparous mothers. This might be related with limited experience of pregnancy, danger signs, labor, and delivery, delay in health-seeking, and high risk for prolonged labor, induction of labor, and birth asphyxia among primaprous.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with several studies, 16 , 19 , 22 , 30 we found that NNM was higher among primiparous mothers. This might be related with limited experience of pregnancy, danger signs, labor, and delivery, delay in health-seeking, and high risk for prolonged labor, induction of labor, and birth asphyxia among primaprous.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is in line with findings in Ethiopia [Hawassa (33.4%) 15 and Debre Tabor (32.9%) 16 ] and Brazilian university hospitals (30.3%). 18 However, it is higher than some other studies in Ethiopia [Jimma (26.7%) 14 and Injibara (23.3%) 19 ], Nepal (7.9%), 20 Brazil [(8.7%), 21 (22.2%), 22 (3.3%) 23 ], and the WHOMCS (7.3%). 6 This might be related with differences in sociodemographic conditions and mothers’ ability of early recognition of complications and health-seeking behavior, study settings, and NNM identification criteria.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…El estudio de corte transversal retrolectivo de Tassew et al (2020), con 422 neonatos y 32.2% de casos de MNE, mostró asociación similar con controles prenatales deficientes, procedencia lejana y parto instrumentado; estos mismos autores también reportaron importancia de otros factores como ser primigestantes, hipertensión asociada al embarazo y hemorragia anteparto (eventos de MME) (29). Gebrehana et al (2020), también realizaron un estudio de corte transversal, con 404 neonatos y 23.3% de casos de MNE, encontrando asociación similar con datos clínicos (parto instrumentado, primigestantes y ruptura prematura de membranas); reportaron asociación con casos remitidos de otras instituciones (30). Por último, un estudio de cohorte realizado por Tekelab et al (2020), con 2,704 nacidos vivos y 122 casos de MNE, reportó una tasa de MNE de 45 casos por cada 1,000 nacidos vivos y mostró asociación con un nivel socioeconómico bajo, periodos intergenésicos cortos y la MME (que suele estar directamente relacionada con el control prenatal) (31).…”
Section: Discussionunclassified